2019
DOI: 10.1186/s13041-019-0501-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-212-5p attenuates ferroptotic neuronal death after traumatic brain injury by targeting Ptgs2

Abstract: Ferroptosis, a newly discovered form of iron-dependent regulated cell death, has been implicated in traumatic brain injury (TBI). MiR-212-5p has previously been reported to be downregulated in extracellular vesicles following TBI. To investigate whether miR-212-5p is involved in the ferroptotic neuronal death in TBI mice, we first examined the accumulation of malondialdehyde (MDA) and ferrous ion, and the expression of ferroptosis-related molecules at 6 h, 12 h, 24 h, 48 h and 72 h following controlled cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 73 publications
4
105
0
Order By: Relevance
“…Inhibiting the ability of PEBP1/15LO complexes to form 15-HpETE-PE may lead to novel anti-ferroptosis approaches and potential neuroprotective drugs. In addition to regulating ferroptosis indicators such as desferrioxamine, vitamin E, U0126, ferrostatin-1, and liproxstatin-1 to regulate ferroptosis, Xiao et al (2019) demonstrated that the administration of miR-212-5p significantly improved learning and spatial memory in a controlled cortical impact model, and the same result was observed in HT-22 and neuro-2a cell lines. The mechanism may reflect miR-212-5p protection against neuronal ferroptosis by targeting Ptgs2 in vivo and in vitro TBI models.…”
Section: Traumatic Brain Injurymentioning
confidence: 66%
“…Inhibiting the ability of PEBP1/15LO complexes to form 15-HpETE-PE may lead to novel anti-ferroptosis approaches and potential neuroprotective drugs. In addition to regulating ferroptosis indicators such as desferrioxamine, vitamin E, U0126, ferrostatin-1, and liproxstatin-1 to regulate ferroptosis, Xiao et al (2019) demonstrated that the administration of miR-212-5p significantly improved learning and spatial memory in a controlled cortical impact model, and the same result was observed in HT-22 and neuro-2a cell lines. The mechanism may reflect miR-212-5p protection against neuronal ferroptosis by targeting Ptgs2 in vivo and in vitro TBI models.…”
Section: Traumatic Brain Injurymentioning
confidence: 66%
“…On analyzing the miRNA profiles, 12 upregulated and 47 downregulated miRNAs were discovered upon melatonin treatment. Among the upregulated miRNAs (Table 1), miR-212-5p was reported to attenuate ferroptotic cell death partially by targeting Ptgs2 in Neuro-2a cell lines (Xiao et al, 2019). The overexpression of miR-138-5p reduces neurological impairment and confers neuroprotection to astrocytes following ischemic stroke (Deng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also showed a preponderance of 15-LOX products in CCI-injured adult mice, and increased ACSL4 and 15-LOX2 expression in TBI, when compared with naive groups ( Kenny et al, 2019 ). Moreover, numerous experimental and clinical studies observed the increased levels of MDA and 4-HNE in either the injured brain or serum following TBI ( Hall et al, 2004 ; Readnower et al, 2010 ; Lorente et al, 2015 ; Xiao et al, 2019 ; Xie et al, 2019 ). As for the morphological features, Xie et al (2019) first verifiably identified the ferroptotic features around brain injury lesions of TBI models at 3 days after CCI.…”
Section: The Role and Mechanism Of Ferroptosis In Acute Cns Injuriesmentioning
confidence: 99%
“…Moreover, a recent study demonstrated the role of miR-212-5p in suppressing ferroptosis after TBI, partially by targeting PTGS2 ( Xiao et al, 2019 ). Further results showed that intracerebroventricular injection of miR-212-5p agomir improved spatial memory and learning in CCI mice, suggesting that miR-212-5p may serve as a potential ferroptosis inhibitor to be used in treating TBI.…”
Section: Potential and Emerging Therapy Targeting Ferroptosis In Acutmentioning
confidence: 99%